Supporting Employees’ wellbeing: Exploring the Perspectives of Filipino Wellbeing Coaches and Implications for Workplace Interventions - Tan, Jessel; Tiongco, Allysa Anne Sarmiento; Untalan, Julien Aimee N.; Manaois, Jason (Psikoislamika: Jurnal Psikologi Islam, 2025)
The importance of wellbeing in the workplace is to promote wellness within the organization and to protect individuals' wellbeing. The study interviewed three wellbeing coaches, selected based on their professional licenses, and extensive field experience in coaching, with at least two years of counseling practice. Purposive sampling was employed to improve data accuracy and relevance selecting experienced individuals to ensure valuable perspectives. Using deductive thematic analysis, Filipino wellbeing coaches present their experiences, and the study used four predetermined key themes following the (ICF) Core Competencies Model which includes foundation, co-creating the relationship, communicating effectively, and cultivating learning and growth. In addition, the key themes were supported by eight sub-themes from the same model. The study discovered that wellbeing coaches provide psychological wellness strategies, implement interventions that integrate various tools and approaches to meet client needs while adhering to ethical practices, and provide continuous individual support which can substantially strengthen organizational efficacy. Wrike (2024) mentioned that organizational development interventions help to improve efficiency and boost employee engagement and satisfaction. Personalized support plans can be created, which may increase engagement, foster a strong culture, and promote innovation. In addition, integrating mental health and wellbeing programs, such as counseling services, stress management workshops, and wellness initiatives, benefits employees' mental health, resulting in increased resiliency. Future studies should include longitudinal studies to evaluate the long-term impact of personalized support plans and diverse tools on employee performance and organizational outcomes. Comparative analysis of different instruments and approaches can provide insights into which methods are most effective.